EMPOWERING EMPLOYEES THROUGH INNOVATIVE HUMAN RESOURCE MANAGEMENT PRACTICES IN THE AGE OF REMOTE WORK - Mashudi Mashudi; Aprilya Fitriani; Nurhamzah Nurhamzah; Radi Radi; Iman Ahmad Gymnastiar (Branding: Jurnal Manajemen dan Bisnis, 2024)
The era of remote work has significantly changed the way companies operate, with a focus on flexibility and innovative use of technology. In this context, human resource management (HR) practices become critical in influencing employee engagement and productivity. The challenges arising from the transition to remote work demand innovation in management approaches, especially in terms of employee empowerment and development. The aim of this research is to explore the effectiveness of innovative HR management practices in empowering employees in the era of remote work. This research was conducted using a qualitative approach, with data obtained from literature studies and relevant previous research. Data analysis was carried out in depth to identify the impact of this practice on employee performance and satisfaction. The conclusion shows that adapting innovative HR management policies and practices can improve operational efficiency and employee satisfaction. The implementation of adaptive management strategies and the use of technology play an important role in ensuring effective communication and accurate performance monitoring in unconventional work environments. Additionally, increasing employee engagement and motivation can be achieved through reward and recognition initiatives and involving them in decision making. Employee skills development and well-being have also proven critical in maintaining and increasing productivity in remote work settings. This study confirms the need for organizations to continuously adapt and update their HR management practices to remain relevant and effective in the digital era.